2011
DOI: 10.1371/journal.pone.0019461
|View full text |Cite
|
Sign up to set email alerts
|

Added Value of Deep Sequencing Relative to Population Sequencing in Heavily Pre-Treated HIV-1-Infected Subjects

Abstract: ObjectiveTo explore the potential of deep HIV-1 sequencing for adding clinically relevant information relative to viral population sequencing in heavily pre-treated HIV-1-infected subjects.MethodsIn a proof-of-concept study, deep sequencing was compared to population sequencing in HIV-1-infected individuals with previous triple-class virological failure who also developed virologic failure to deep salvage therapy including, at least, darunavir, tipranavir, etravirine or raltegravir. Viral susceptibility was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 23 publications
3
33
0
Order By: Relevance
“…The impact of low-frequency drug-resistant HIV-1 variants on treatment outcomes in patients is a matter of great debate (32,34,(38)(39)(40)(41)72). Several studies suggest that preexisting minority drugresistant variants in treatment-naive patients have minimal to no effect on the treatment outcome even if the treatment involves drugs associated with the drug resistance pattern (e.g., treatment with NVP when a patient has 3% NVP-resistant variants) (32,49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of low-frequency drug-resistant HIV-1 variants on treatment outcomes in patients is a matter of great debate (32,34,(38)(39)(40)(41)72). Several studies suggest that preexisting minority drugresistant variants in treatment-naive patients have minimal to no effect on the treatment outcome even if the treatment involves drugs associated with the drug resistance pattern (e.g., treatment with NVP when a patient has 3% NVP-resistant variants) (32,49).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, a series of ultrasensitive HIV-1-genotyping assays, based on deep sequencing (next-generation sequencing [NGS]), have been developed to detect drug-resistant HIV-1 variants at levels below 20% of the viral population in an infected individual (24,(28)(29)(30)(31). Several studies have associated early detection of these minority HIV-1 drug-resistant variants with subsequent treatment failure (32)(33)(34)(35)(36)(37); however, with the advent of single-pill once-a-day (QD) cART regimens, treatment failures in HICs are rare, and the relevance of minority members of the viral population to the ART outcome is still under debate (32,(38)(39)(40)(41).…”
mentioning
confidence: 99%
“…As described above, DeepGen HIV detected additional (minority) HIV-1 drug resistance mutations and non-R5 variants compared to population sequencing; however, the clinical relevance of these minority members of the viral population is still under debate (33,51,55,57,(127)(128)(129). It is reasonable to assume that under appropriate selection (i.e., drug pressure), minority variants carrying drug resistance mutations will eventually outcompete other members of the viral population, and the earlier these mutations are detected, the sooner the proper strategy can be defined to control the growth of these viruses.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies demonstrated that drug-resistance mutations detected by 454 had a significant impact on virological failure [103][104][105][106][107] while others did not find a strong association of low-frequency mutations with clinical responses [108,109]. Deep sequencing using the 454 platform has been also applied to investigate drug-resistance mutations against the more recently approved integrase inhibitors and CCR5 antagonists.…”
Section: Monitoring Antiviral Drug Resistancementioning
confidence: 99%